Туристическая индустрия Турции: становление и перспективы развития - Мираньков, Д.Б.; Никитина, М.Г. (Культура народов Причерноморья, 2014)
В статье рассмотрен турецкий опыт становления туристической отрасли в условиях
трансформации экономики. Проанализировано современное состояние и выявлены перспективные
направления развития туристической индустрии Республики Турция. У статті розглянуто турецький досвід становлення туристичної галузі в умовах трансформації
економіки. Проаналізовано сучасний стан та виявлено перспективні напрямки розвитку туристичної
індустрії Республіки Туреччина. The development of the tourism sector in Turkey after the collapse of the Ottoman Empire and the
establishment of the Republic should be considered in the context of the overall economic development of the country,
which directly affects the economic policy of the different governments of the Republic of Turkey.
During the period of nationalist politics (1924-1950 years), the government does not pay considerable attention to the
development of the tourism sector. During the protectionist policies of liberalism (1950-1960 years) in the tourism
sector breakthrough did not happen, because it attracts large investments necessary condition is the development of
appropriate infrastructure, which at that time did not exist. However, in the period of planned economy (1960-1980
years) income from the tourism sector increased by 25 times. In the 80 years the Turkish government adopted a series
of initiatives, which gave a powerful impetus to the growth of the tourism sector.
Currently, the tourism industry is one of the three most dynamic sectors of the Turkish economy. Turkish government
developed a «Strategy of the Turkish Tourism – 2023» envisages further development of the infrastructure, attract
foreign investment and entry of Turkey into the top five countries in the world tourism.